Pengaruh Video Pembelajaran melalui Zenius.Net terhadap Hasil Belajar Kognitif Biologi Siswa Madrasah Aliyah Kelas X dan XI - Baiq Rina Amalia Safitri; Fitri Astutik; Ahmad Nabil Fikri; Saudiah Saudiah (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The use of media in the learning process can generate motivation and stimulus in learning activities, and even bring psychological effects on students. The purpose of this study was to determine the effect of learning videos through Zenius.Net on cognitive biology learning outcomes for students of Madrasah Aliyah class X and XI. The type of research used is descriptive quantitative, which was carried out with a pre-experimental research method using a one group pretest posttest research design. The research sample was students of MAS Al-Anshor Beber, Pengenjek Village, Jonggat District, Central Lombok Regency as many as 17 students. The sampling technique used is a non-probability sampling technique. Data were analyzed by normalized N-gain method and paired samples t-test. Based on the results of data analysis, the pretest value was 34.4, while the posttest value was 78.6. This shows an increase in student cognitive learning outcomes (gain) by 44.2. The n-gain value is 0.7 which indicates the medium category. These results indicate that the use of video media in Biology science learning has an influence on the ability of students' cognitive learning outcomes. Furthermore, the hypothesis test is obtained tcount = 24.61 > tcritical = 2.12, then Ha is accepted, namely learning videos through Zenius.Net can improve students' cognitive learning outcomes.